Absorbed Pb2+ and Cd2+ Ions in Water by Cross-Linked Starch Xanthate - Kai Feng; Guohua Wen (International Journal of Polymer Science)
A cross-linked starch xanthate was prepared by graft copolymerization of acrylamide and sodium acrylate onto starch xanthate using potassium persulfate and sodium hydrogen sulfite initiating system and N,N′-methylenebisacrylamide as a cross-linker. As this kind of cross-linked potato starch xanthate can effectively absorb heavy metal ions, it was dispersed in aqueous solutions of divalent heavy metal ions (Pb2+ and Cd2+) to investigate their absorbency by the polymer. Factors that can influence absorbency were investigated, such as the ratio of matrix to monomers, the amount of initiator and cross-linker, pH, and the concentration of metal ions. Results were reached and conclusion was drawn that the best synthetic conditions for the polymer adsorbing Pb2+ and Cd2+ were as follows: the quality ratio of matrix to monomers was 1 : 12 and 1 : 11, the amount of initiator was 2.4% and 3.2% of matrix, and the amount of cross-linker was 12 mg and 13 mg. When the initial concentration of ions was 10 mg/L, the highest quantities of adsorption of Pb2+ and Cd2+ were 47.11 mg/g and 36.55 mg/g. Adsorption mechanism was discussed by using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscope (SEM), Energy Dispersive X-Ray Spectroscopy (EDS) test, and adsorption kinetic simulation.